2022
DOI: 10.33736/ijbs.4842.2022
|View full text |Cite
|
Sign up to set email alerts
|

Cashless Payments and Banking Performances: A Study of Local Commercial Banks in Malaysia

Abstract: The banking industry plays a facilitatory role in moving toward a cashless society. This study investigates the impacts of cashless payments (ATM, internet banking, mobile banking, credit card, debit card, charge card and e-money) on banking performance for eight local commercial banks in Malaysia over the period of 2005 to 2018. The findings show that cashless payments are positively related to the return on assets (ROA) and return on equity (ROE) of banks, except e-money. Furthermore, the study demonstrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…These findings are confirmed by Nikabadi and Mousavi (2016). In contrast, Lu (2022) shows that cashless payment systems have no obvious effect over time on how efficiently banks operate.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…These findings are confirmed by Nikabadi and Mousavi (2016). In contrast, Lu (2022) shows that cashless payment systems have no obvious effect over time on how efficiently banks operate.…”
Section: Resultsmentioning
confidence: 73%
“…Policymakers should be inspired by fintech businesses to provide more convenient services and more individualized consumer experiences. In a society without cash, cooperation between these two parties can result in a win-win situation, (Lu, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al 2023;Zhao et al 2022). A solitary paper used mixed methods to combine linear and non-linear approaches (Lu 2022;Chhaidar et al 2022) (Table 5 and Figure 4). Total:…”
Section: Resultsmentioning
confidence: 99%
“…The ATM ratio is a component of the technological infrastructure assets and signifies investments in Information Technology (IT) (Del Gaudio et al 2021). The SLR uncovered that four articles (Adalessossi 2023;Lu 2022;Del Gaudio et al 2021;Bashayreh and Wadi 2021) had utilized the ATM ratio to indicate Fintech at the bank level. Two studies (Del Gaudio et al 2021;Bashayreh and Wadi 2021) showed that a higher ATM ratio contributed to enhanced bank profitability, whereas the other two studies (Adalessossi 2023;Lu 2022) observed the contrary effect.…”
Section: Measuring Fintech Using Bank-level Datamentioning
confidence: 99%
See 1 more Smart Citation